Governance structure and external audit price: evidence from an emerging economy - Muhamad Sori, Zulkarnain; Mohamad, Shamsher (Faculty of Economics and Management, Universiti Putra Malaysia, 2008)
This study provides new evidence on the relationship between external audit price and corporate governance of the largest (based on market capitalization) 100 listed firms on both the main and second board of the Bursa Malaysia (BMB) (previously known as the Kuala Lumpur Stock Exchange). The findings show that for main board companies, external audit price is positively and significantly associated with corporate size, complexity and internal governance variable (i.e. director’s remuneration). For the second board firms, complexity, corporate size and internal governance variables (i.e. proportion of non-executive directors to total directors) were important determinants of external audit pricing. External audit price had a significant negative relationship with individual shareholders ownership for both main and second board companies, and companies’ age for companies listed on the second board.